An Aesthetic “Touch” for the Development of Rattan Bag Handicraft Products in Indonesia: A Systematic Literature Review - Cahyadi, Dwi; Ismail, Siti Haida; Mohammad, Roslina; MD Daud, Mohd Yusof; Irwan, Muh (Harmonia: Journal of Arts Research and Education, 2024)
One of the crucial factors in Indonesia’s National Industrial Development Master Plan 2015 - 2035 is enhancing human resources skills and creativity in producing wood/rattan handicrafts. Aesthetic factors are the main requirements for these products due to their cultural and artistic value. In determining the direction of the innovations, it is necessary to understand the product’s development, especially in this regard. Therefore, this study aimed to assess the aesthetic factors used in developing rattan bag handicraft products using the Systematic Literature Review (SLR) approach, guided by Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). The SLR was conducted based on the journal and proceedings obtained through the Science Direct, Google Scholar, and Springer databases. The contribution of this study was to find aesthetic factors considered for the development of bag product innovation. The results showed that six aesthetic factors were applied in developing rattan bag products: materials, motifs, ethnic/culture, shapes, patterns, and colors.